Hydrodeoxygenation catalyst for biological oil and fat as well as preparation and application of hydrodeoxygenation catalyst
By using spinel composite oxide-supported Ni2P catalyst, the problems of poor stability and high cost of hydrodeoxygenation catalysts of bio-oils are solved, and efficient biodiesel preparation is achieved, with excellent conversion and selectivity, and vulcanization treatment is avoided. It is suitable for Industrialized production.
Patent Information
- Application Number
- CN202310706819.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing bio-oil hydrodeoxygenation catalysts have problems such as poor stability, complex preparation and high cost. They are especially prone to inactivation or need vulcanization treatment when used in high-pressure fixed bed reactors, which increases production costs.
Using spinel composite oxide as support and Ni2P as the active component catalyst, it is prepared by co-precipitation method and calcination reduction method, which avoids vulcanization treatment and is used in high-pressure drip bed reactors, improving the stability of the catalyst and selective.
It has achieved efficient hydrodeoxygenation and deoxygenation of bio-oils, with a conversion rate of up to 94%, a selectivity of n-C15 to C18 is higher than 73%, an oil yield of more than 71%, and a catalyst is stable under hydrothermal conditions, which is prolonged. Service life reduces energy consumption and subsequent processing costs.
Smart Images

Figure CN119140132A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the new technical field of bioenergy, and specifically relates to a preparation method and application of a catalyst for catalyzing the hydrogenation and deoxygenation of bio-oil. Background Art
[0002] With the increasing consumption of non-renewable resources, the rising prices of fossil energy and increasingly stringent environmental protection requirements, energy shortages and energy conservation and emission reduction have constrained economic development, and people have begun to look for and develop green and environmentally friendly energy.
[0003] Bio-oil is a rich and renewable resource and a potential new energy source. The main component of bio-oil is higher fatty acid esters, which have a large relative molecular weight and high oxygen content (generally up to 35% to 60%). Therefore, it must be hydrodeoxygenated and refined to reduce the oxygen content and improve its quality before it can be used as vehicle fuel and aviation kerosene.
[0004] Chinese patent CN 101709225 A discloses a method of using sunflower oil as raw material and using 2% Pd / BaSO 4 The catalyst was reacted in a reactor at 270°C, 3.0MPa, and for 7h, the conversion rate of sunflower oil could reach 100%, and the product was long-chain alkane. However, precious metals are expensive and have limited reserves, so large-scale industrial applications are restricted.
[0005] Chinese patent CN103721741 A discloses a catalyst and a method for using castor oil to produce biodiesel by hydrodeoxygenation. In a high-pressure fixed-bed reactor, castor oil can be hydrodeoxygenated to produce biodiesel, but metal phosphides are used as catalysts, which are complicated to prepare and are easily deactivated in the presence of water.
[0006] Chinese patent CN 101270300 A discloses a sulfided Ni-Mo / TiO 2 -Al 2 O 3 As a biodiesel hydrodeoxygenation catalyst, the catalyst shows good hydrodeoxygenation performance, but sulfur loss occurs during the reaction process, and sulfur reagents need to be continuously replenished to maintain the high stability of the catalyst; in addition, since the hydrodeoxygenation product contains sulfur, it also needs to be subsequently desulfurized, which increases production costs.
[0007] In recent years, studies have found that transition metal phosphides have become a hot topic in the research of new hydrogenation catalysts due to their high hydrodesulfurization and hydrodenitrogenation activities. 2P has excellent precious metal-like properties and has attracted widespread attention. It not only has good resistance to carbon deposition and poisoning, but also has high hydrogenation activity. In addition, most of the existing oil and fat hydrodeoxygenation catalysts use alumina as a carrier. Due to the high reaction temperature, a large amount of water is generated during the hydrodeoxygenation process, and alumina is prone to hydration, resulting in poor catalyst stability. Spinel-type composite oxides are a high-melting-point substance with high mechanical strength and anti-hydration properties. They are widely used as carriers in the catalytic field. Since the preparation process of spinel is relatively simple and inexpensive, it is of great significance to apply it to the hydrodeoxygenation of bio-oils to improve the stability of the catalyst. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a supported bio-oil hydrodeoxygenation catalyst in view of the above-mentioned deficiencies in the prior art. The preparation method is simple, has high catalytic activity, good selectivity, high oil yield, and maintains high stability during use.
[0009] In order to solve the above problems, the catalyst used in the present invention is a spinel composite oxide as a carrier, with Ni 2 P is a supported catalyst with an active component, and the active component Ni 2 P accounts for 2 to 40% of the total mass of the catalyst, preferably 5 to 35%, more preferably 10 to 30%.
[0010] The preparation method of the catalyst comprises the following steps: preparing spinel composite oxide by coprecipitation method, then loading soluble nickel salt and phosphate salt, and preparing spinel loaded Ni by calcination and reduction. 2 P catalyst.
[0011] The preparation method of the spinel composite oxide carrier is as follows: dissolving one of soluble metal nickel, cobalt, magnesium or copper salts and aluminum salt in deionized water to obtain a mixed solution, wherein the molar ratio of the sum of one or more of nickel, cobalt, magnesium or copper to aluminum is 1:1.5 to 1:5, preferably 1:1.8 to 1:4, and more preferably 1:2 to 1:3, slowly dropping a precipitant solution into the mixed solution, and performing a precipitation reaction at 30 to 90° C. When the pH of the solution reaches 8 to 12, stopping the dropping of the precipitant solution, continuing stirring for 0.5 to 6 hours, and then filtering, washing, drying and calcining in sequence to obtain the spinel composite oxide carrier.
[0012] The catalyst supports the active component Ni 2The preparation method of P is as follows: dissolving a soluble nickel salt and a phosphate salt in water, wherein the molar ratio of nickel ions to phosphate ions is 3:1 to 1:3, preferably 2.5:1 to 1:2.5, more preferably 2:1 to 1:2, to form an impregnation solution; adding a spinel carrier to the impregnation solution for impregnation, drying, roasting and reducing, to obtain a spinel-loaded Ni 2 P catalyst.
[0013] The soluble nickel salt is nickel nitrate, nickel chloride, nickel sulfate or nickel acetate.
[0014] The soluble cobalt salt is cobalt nitrate, cobalt chloride, cobalt sulfate or cobalt acetate.
[0015] The soluble magnesium salt is: magnesium nitrate, magnesium chloride, magnesium sulfate or magnesium acetate.
[0016] The soluble copper salt is: copper nitrate, copper chloride, copper sulfate or copper acetate.
[0017] The soluble aluminum salt is aluminum nitrate, aluminum chloride or aluminum sulfate.
[0018] The precipitant is selected from NaOH, Na 2 CO 3 , KOH, K 2 CO 3 The mass concentration of the precipitant is 2 to 30%, preferably 5 to 25%, and more preferably 8 to 20%.
[0019] The spinel composite oxide precursor is dried at 100-120°C for 8-14h, and calcined in a muffle furnace at 600-1000°C, preferably 700-900°C, more preferably 750-850°C, for 4-10h, preferably 5-9h, more preferably 6-8h.
[0020] The soluble phosphate salt is diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium hypophosphite, potassium hypophosphite or ammonium hypophosphite, and the mass concentration of the phosphate salt in water is 0.5-30%, preferably 1-20%, and more preferably 2-15%.
[0021] The catalyst precursor drying, calcining and reducing process is as follows: drying at 60-80°C for 12h; calcining at 50-500°C, preferably 100-400°C, more preferably 200-300°C under nitrogen for 1-10h; then reducing at 100-800°C, preferably 200-700°C, more preferably 400-600°C under hydrogen for 1-10h, cooling to room temperature, and passivating under nitrogen for 1-10h to obtain spinel-loaded Ni 2 P catalyst.
[0022] The catalyst is reduced with hydrogen before the reaction, under the following conditions: normal pressure, 150-300°C, pure hydrogen, reduction for 2-6h;
[0023] The application of the bio-oil hydrodeoxygenation catalyst in a high-pressure trickle bed reactor is as follows: the reaction temperature is 250-400°C, the reaction pressure is 1-10 MPa, the hydrogen-oil ratio is 200-2000:1, and the liquid hourly space velocity is 0.2-5 h -1 Under the conditions of high temperature, oxygen-rich bio-oil can be efficiently converted into normal alkanes.
[0024] The biological oil is one or more of soybean oil, palm oil, olive oil, peanut oil, jatropha oil, rapeseed oil, cottonseed oil, castor oil and tung oil.
[0025] The beneficial effects of the present invention are as follows:
[0026] 1. The present invention adopts Ni 2 P / spinel composite oxide catalyst catalyzes the hydrodeoxygenation of bio-oil to produce normal alkanes. Spinel as a carrier has strong mechanical strength and anti-hydration stability, and the active component Ni 2 P exhibits precious metal-like properties. Through the synergistic effect of the carrier and nickel phosphide, the catalyst exhibits high hydrogenation activity and selectivity for the target product. Since the catalyst does not require sulfurization during use, the reaction energy consumption and the subsequent product processing cost are greatly reduced.
[0027] 2. The catalyst of the present invention uses soybean oil in biological oil as a model reaction, and the conversion rate of soybean oil can reach more than 94%, and the highest can reach 100%. 15 ~C 18 The total selectivity is above 73%, the oil yield is greater than 71%, and the highest can reach 82.6%. The catalyst has good activity, high selectivity for the target product, and stable catalyst performance during the reaction. It can replace petrochemical diesel and is an optional technical route for producing high-quality aviation kerosene.
[0028] nC in the normal alkanes in the product 15 ~C 18 The catalyst of the present invention has stable surface properties, improves the stability of the catalyst under hydrothermal conditions, and prolongs the service life of the catalyst. In addition, the catalyst does not require sulfurization, avoids the pollution of subsequent products by traditional sulfurized catalysts, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 For the nickel aluminum spinel carrier and the supported Ni in Example 1 2 P / NiAl 2 O 4 XRD spectra of catalyst and high temperature calcined alumina;
[0030] Figure 2 This is a graph showing the experimental results of soybean oil conversion rate of the catalysts in Example 1 and Comparative Example 1 after 500 hours of reaction. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0032] Example 1
[0033] a. Preparation of nickel aluminum spinel support
[0034] (1) 60 g of nickel nitrate, 154.8 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0035] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0036] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 2 hours;
[0037] (4) The precipitate is filtered, washed with water, and the filter cake is dried at 120° C. for 12 h, and calcined at 800° C. for 6 h to allow nickel oxide and aluminum oxide to undergo a solid phase reaction to obtain a nickel aluminum spinel catalyst carrier. Figure 1 The XRD spectra of the nickel aluminum spinel catalyst support and high temperature calcined alumina (800℃, 6h) are given. The characteristic diffraction peaks of alumina appear at 2θ=37°, 45.1° and 65.7°, while after the catalyst precursor is calcined at high temperature, stronger diffraction peaks appear at 2θ=37°, 45.1° and 65.7°, which is NiAl 2 O 4 The characteristic peaks of spinel and no NiO were detected, indicating that the Ni atoms completely entered the gaps between the tetrahedron and octahedron of alumina during high temperature calcination to form a stable Ni-Al-O spinel structure. The carrier number is NiAl 2 O 4 -1.
[0038] b. 10% Ni 2 P / NiAl 2 O 4 Catalyst preparation
[0039] 13.1 g of nickel nitrate and 3.2 g of disodium hydrogen phosphate were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of nickel aluminum spinel carrier (numbered NiAl 2 O 4-1) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 250°C for 2 hours under nitrogen, reduced at 500°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 10% Ni 2 P / NiAl 2 O 4 Catalyst (10% of which represents the active component Ni 2 The mass of P accounts for % of Ni 2 P / NiAl 2 O 4 10% of the total mass of the catalyst, the same below). Figure 1 Also gives 5% Ni 2 P / NiAl 2 O 4 The XRD spectrum of the catalyst shows Ni at 2θ = 40.5°, 44.8° and 47.5°. 2 The characteristic diffraction peak of P, no other metal phosphide was detected in the figure. The catalyst number is CAT-1.
[0040] Example 2
[0041] a. Preparation of nickel aluminum spinel support
[0042] (1) 53.4 g of nickel chloride, 110.2 g of aluminum chloride and 300 ml of deionized water were mixed to prepare a mixed solution;
[0043] (2) adding 15 wt % sodium carbonate solution dropwise to the mixed solution prepared in step (1) at 60° C. with stirring;
[0044] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0045] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow nickel oxide and aluminum oxide to undergo a solid phase reaction to obtain a nickel aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=37°, 45.1° and 65.7°, which belonged to NiAl 2 O 4 The characteristic peaks of the spinel structure, and no NiO was detected, the carrier number is NiAl 2 O 4 -2.
[0046] b. 15% Ni 2 P / NiAl 2 O 4 Dehydrogenation catalyst preparation
[0047] 16.9 g of nickel chloride and 4.68 g of diammonium hydrogen phosphate were dissolved in 30 ml of deionized water to form an impregnation solution; 30 g of nickel aluminum spinel carrier (numbered NiAl 2 O 4 -2) added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 120°C for 10 hours, calcined at 300°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 15% Ni 2 P / NiAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-2.
[0048] Example 3
[0049] a. Preparation of nickel aluminum spinel support
[0050] (1) 36.5 g of nickel acetate, 99.69 g of aluminum chloride and 300 ml of deionized water were mixed to prepare a mixed solution;
[0051] (2) adding 10 wt % potassium hydroxide solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0052] (3) When the pH value of the solution reaches 8, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 2 hours;
[0053] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 900°C for 6 hours to allow nickel oxide and aluminum oxide to react in a solid phase to obtain a nickel aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=37°, 45.1° and 65.7°, which belonged to NiAl 2 O 4 The characteristic peaks of the spinel structure, and no NiO was detected, the carrier number is NiAl 2 O 4 -3.
[0054] b. 20% Ni 2 P / NiAl 2 O 4 Dehydrogenation catalyst preparation
[0055] 17.9 g of nickel acetate and 4.2 g of ammonium hypophosphite were dissolved in 30 ml of deionized water to form an impregnation solution; 30 g of nickel aluminum spinel carrier (numbered NiAl 2 O 4-3) added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 120°C for 10 hours, calcined at 300°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 20% Ni 2 P / NiAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-3.
[0056] Example 4
[0057] a. Preparation of Cobalt Aluminum Spinel Support
[0058] (1) 60 g of cobalt nitrate, 154.8 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0059] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at a temperature of 60° C. with stirring;
[0060] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0061] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow cobalt oxide and aluminum oxide to react in a solid phase to obtain a cobalt aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.4°, 37° and 65.4°, which belonged to CoAl 2 O 4 The characteristic peaks of the spinel structure, and no CoO was detected, the carrier number is CoAl 2 O 4 -4.
[0062] b. 10% Ni 2 P / CoAl 2 O 4 Catalyst preparation
[0063] 13.1 g of nickel nitrate and 3.2 g of disodium hydrogen phosphate were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of cobalt aluminum spinel carrier (numbered CoAl 2 O 4 -4) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 250°C for 2 hours under nitrogen, reduced at 500°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 10% Ni 2 P / CoAl2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-4.
[0064] Example 5
[0065] a. Preparation of Cobalt Aluminum Spinel Support
[0066] (1) 60 g of cobalt nitrate, 154.8 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0067] (2) adding 10 wt % potassium hydroxide solution dropwise to the mixed solution prepared in step (1) at 90° C. with stirring;
[0068] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 90°C, and age the precipitate for 2 hours;
[0069] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow cobalt oxide and aluminum oxide to react in a solid phase to obtain a cobalt aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.4°, 37° and 65.4°, which belonged to CoAl 2 O 4 The characteristic peaks of the spinel structure, and no CoO was detected, the carrier number is CoAl 2 O 4 -5.
[0070] b. 20% Ni 2 P / CoAl 2 O 4 Catalyst preparation
[0071] 29.4 g of nickel nitrate and 7.2 g of disodium hydrogen phosphate were dissolved in 60 ml of deionized water to form an impregnation solution; 30 g of cobalt aluminum spinel carrier (numbered CoAl 2 O 4 -5) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 250°C for 2 hours under nitrogen, reduced at 500°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 20% Ni 2 P / CoAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2The diffraction peak of P was not detected in the figure. The catalyst number was CAT-5.
[0072] Example 6
[0073] a. Preparation of Cobalt Aluminum Spinel Support
[0074] (1) 48.8 g of cobalt chloride, 99.1 g of aluminum chloride and 300 ml of deionized water were mixed to prepare a mixed solution;
[0075] (2) adding 15 wt % potassium carbonate solution dropwise to the mixed solution prepared in step (1) at a temperature of 40° C. with stirring;
[0076] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 40°C, and age the precipitate for 2 hours;
[0077] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 900°C for 6 hours to allow cobalt oxide and aluminum oxide to react in a solid phase to obtain a cobalt aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.4°, 37° and 65.4°, which belonged to CoAl 2 O 4 The characteristic peaks of the spinel structure, and no CoO was detected, the carrier number is CoAl 2 O 4 -6.
[0078] b.30%Ni 2 P / CoAl 2 O 4 Dehydrogenation catalyst preparation
[0079] 41.2 g of nickel chloride and 11.4 g of diammonium hydrogen phosphate were dissolved in 60 ml of deionized water to form an impregnation solution; 30 g of cobalt aluminum spinel carrier (numbered CoAl 2 O 4 -6) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 120°C for 10 hours, calcined at 300°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 30% Ni 2 P / CoAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-6.
[0080] Example 7
[0081] a. Preparation of magnesium aluminum spinel carrier
[0082] (1) 79.4 g of magnesium nitrate, 232.2 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0083] (2) adding 10 wt % potassium hydroxide solution dropwise to the mixed solution prepared in step (1) at 60° C. with stirring;
[0084] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0085] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow magnesium oxide and aluminum oxide to react in a solid phase to obtain a magnesium aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.2°, 45.8° and 66.2°, which belonged to MgAl 2 O 4 The characteristic peaks of the spinel structure, and no MgO was detected, the carrier number is MgAl 2 O 4 -7.
[0086] b. 10% Ni 2 P / MgAl 2 O 4 Catalyst preparation
[0087] 13.1 g of nickel nitrate and 2.9 g of diammonium hydrogen phosphate were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of magnesium aluminum spinel carrier (numbered MgAl 2 O 4 -7) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 250°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 10% Ni 2 P / MgAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-7.
[0088] Example 8
[0089] a. Preparation of magnesium aluminum spinel carrier
[0090] (1) 79.4 g of magnesium nitrate, 232.2 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0091] (2) adding 15 wt % sodium carbonate solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0092] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 2 hours;
[0093] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 700°C for 6 hours to allow magnesium oxide and aluminum oxide to react in a solid phase to obtain a magnesium aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.2°, 45.8° and 66.2°, which belonged to MgAl 2 O 4 The characteristic peaks of the spinel structure, and no MgO was detected, the carrier number is MgAl 2 O 4 -8.
[0094] b. 20% Ni 2 P / MgAl 2 O 4 Catalyst preparation
[0095] 29.4 g of nickel nitrate and 4.2 g of ammonium hypophosphite were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of magnesium aluminum spinel carrier (numbered MgAl 2 O 4 -8) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 60°C for 10 hours, calcined at 300°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 20% Ni 2 P / MgAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P is 1.0, and no other metal phosphides are detected in the figure. The catalyst number is CAT-8.
[0096] Example 9
[0097] a. Preparation of copper aluminum spinel carrier
[0098] (1) 49.8 g of copper nitrate, 154.8 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0099] (2) adding 10 wt % sodium hydroxide solution dropwise to the mixed solution prepared in step (1) at 60° C. with stirring;
[0100] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 60°C, and age the precipitate for 2 hours;
[0101] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow copper oxide and aluminum oxide to react in a solid phase to obtain a copper-aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.3°, 36.8°, and 44.8°, which belonged to CuAl 2 O 4 The characteristic peaks of the spinel structure, and no CuO was detected, the carrier number is CuAl 2 O 4 -9.
[0102] b. 10% Ni 2 P / CuAl 2 O 4 Catalyst preparation
[0103] 13.1 g of nickel nitrate and 2.9 g of diammonium hydrogen phosphate were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of copper aluminum spinel carrier (numbered CuAl 2 O 4 -9) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 250°C under nitrogen for 2 hours, reduced at 600°C under hydrogen for 2 hours, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 10% Ni 2 P / CuAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P was not detected in the figure. The catalyst number was CAT-9.
[0104] Example 10
[0105] a. Preparation of copper aluminum spinel carrier
[0106] (1) 49.8 g of copper nitrate, 154.8 g of aluminum nitrate and 600 ml of deionized water were mixed to prepare a mixed solution;
[0107] (2) adding 15 wt % sodium carbonate solution dropwise to the mixed solution prepared in step (1) at a temperature of 80° C. with stirring;
[0108] (3) When the pH value of the solution reaches 10, stop adding dropwise, maintain the temperature of the precipitation system solution at 80°C, and age the precipitate for 4 hours;
[0109] (4) The precipitate was filtered, washed, and the filter cake was dried at 120°C for 12 hours and calcined at 800°C for 6 hours to allow copper oxide and aluminum oxide to react in a solid phase to obtain a copper-aluminum spinel catalyst carrier. XRD analysis showed strong diffraction peaks at 2θ=31.3°, 36.8°, and 44.8°, which belonged to CuAl 2 O 4 The characteristic peaks of the spinel structure, and no CuO was detected, the carrier number is CuAl 2 O 4 -10.
[0110] b. 10% Ni 2 P / CuAl 2 O 4 Catalyst preparation
[0111] 13.1 g of nickel nitrate and 1.8 g of ammonium hypophosphite were dissolved in 45 ml of deionized water to form an impregnation solution; 30 g of copper aluminum spinel carrier (numbered CuAl 2 O 4 -10) was added to the impregnation solution and impregnated at room temperature for 2 hours; the obtained product was dried at 80°C for 10 hours, calcined at 300°C for 2 hours under nitrogen, reduced at 600°C for 2 hours under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1 hour to obtain 10% Ni 2 P / CuAl 2 O 4 The catalyst was analyzed by XRD, where Ni 2 The diffraction peak of P is 1.0, and no other metal phosphides are detected in the figure. The catalyst number is CAT-10.
[0112] Comparative Example 1
[0113] Preparation of 20% Ni / alumina catalyst
[0114] Dissolve 37.2g of nickel nitrate in 50ml of deionized water to form an impregnation solution; 2 O 3 (pre-calcined at 800°C for 6h) was added to the impregnation solution, impregnated at room temperature for 2h, dried at 120°C for 10h, and calcined at 400°C for 2h; then reduced at 400°C for 2h under hydrogen, cooled to room temperature, and then passivated under nitrogen for 1h to obtain a 20% Ni / alumina catalyst.
[0115] In order to demonstrate the beneficial results of the present invention, the inventors used soybean oil hydrodeoxygenation in the bio-oil model compound to prepare normal alkanes as the reaction system, and loaded Ni on the spinel composite oxides prepared in Examples 1 to 10 respectively. 2The hydrodeoxygenation performance of the catalyst P and the catalyst prepared in Comparative Example 1 was evaluated. Catalyst reduction: 4 ml of catalyst, normal pressure, 250°C, pure hydrogen, space velocity 1000 h -1 , reduction for 4h; hydrogenation reaction: reaction temperature 340℃, pressure 5.0MPa, liquid hourly space velocity 1.0h -1 , hydrogen to oil volume ratio 1000:1, after 24h reaction, sampling and analysis. Agilent 7890B gas chromatograph was used to analyze the samples, FID detector. The conversion rate and nC of soybean oil were calculated according to the area normalization method. 15 ~C 18 The total selectivity of normal alkanes is shown in Table 1.
[0116] Table 1 Hydrodeoxygenation performance of different catalysts
[0117]
[0118] Reaction conditions: temperature 340°C, pressure 4.0 MPa, liquid hourly space velocity 1.0 h -1 , hydrogen oil volume ratio 1000:1, reaction time 24h
[0119] It can be found from Table 1 that the hydrodeoxygenation catalysts prepared in Examples 1 to 10 are used in the reaction system of soybean oil hydrodeoxygenation to prepare normal alkanes. The catalysts show high reaction activity and selectivity, and the conversion rate of soybean oil is above 94%, and the highest can reach 100%. 15 ~C 18 The total selectivity is above 73%, and the oil yield is greater than 71%, with the highest reaching 82.6%. Comparative Example 1 Compared with Example 1, under the same nickel loading, the conversion rate of soybean oil in Example 1 is 97.2%, nC 15 ~C 18 The total selectivity is 76.3%, and the oil yield is 79.3%; while the conversion rate of soybean oil in Comparative Example 1 is 94.3%, nC 15 ~C 18 The total selectivity is 70.5%, and the oil yield is 71.7%. 2 P Catalyst Reaction Activity, nC 15 ~C 18 The overall selectivity and oil yield are better than the catalytic performance of Comparative Example 1.
[0120] In order to further demonstrate the beneficial effects of the present invention, the inventors conducted a 500-h stability test on the catalysts prepared in Example 1 and Comparative Example 1. The experimental results are shown in Figure 2 .Depend on Figure 2It can be seen that the conversion rate of soybean oil of the catalyst of Example 1 changes little with the extension of reaction time, while the catalyst of Comparative Example 1 decreases slowly in the initial stage of the reaction, and the conversion rate of soybean oil decreases rapidly after 100 hours of reaction. 2 The hydrodeoxygenation catalyst prepared by loading P on a spinel carrier can maintain good reaction activity and stability.
Claims
1. A method for preparing a bio-oil hydrodeoxygenation catalyst, characterized in that: The catalyst is one or two of nickel aluminum spinel, cobalt aluminum spinel, magnesium aluminum spinel or copper aluminum spinel, and the active component Ni2P is loaded on the carrier. The preparation method includes the following steps: (1) Preparing spinel composite oxides by coprecipitation method; (2) loading soluble nickel salt and phosphate salt on the spinel composite oxide, and preparing the spinel-loaded Ni2P catalyst through calcination and reduction; The catalyst active component Ni2P accounts for 2-40% of the total mass of the catalyst, preferably 5-35%, more preferably 10-30%.
2. The preparation method according to claim 1, characterized in that: The catalyst preparation comprises the following steps: (1) A spinel composite oxide carrier is prepared by a coprecipitation method: one or more salts of one or more soluble metals such as nickel, cobalt, magnesium or copper and an aluminum salt are dissolved in water to obtain a mixed solution, wherein the molar ratio of the sum of one or more salts of nickel, cobalt, magnesium or copper to aluminum is 1:2 to 1:5, preferably 1:2 to 1:4, more preferably 1:2 to 1:3, a precipitant solution is added dropwise to the mixed solution under stirring, and a precipitation reaction is carried out at 30 to 90° C. When the pH of the solution reaches 8 to 12, the addition of the precipitant solution is stopped, and stirring is continued for 0.5 to 6 hours. Afterwards, filtering (obtaining a spinel composite oxide precursor), washing, drying and calcining are performed in sequence to obtain a spinel composite oxide carrier; (2) Loading the active component Ni2P: Dissolve soluble nickel salt and phosphate salt in water, wherein the molar ratio of nickel ion:phosphorus ion is 2:1 to 1:3, preferably 2:1 to 1:2.5, more preferably 2:1 to 1:2, to form an impregnation solution; add a spinel carrier into the impregnation solution for impregnation (to obtain a catalyst precursor), dry, calcine and reduce, to obtain a spinel-loaded Ni2P catalyst.
3. The preparation method according to claim 1 or 2, characterized in that: The soluble nickel salt is one or more of nickel nitrate, nickel chloride, nickel sulfate or nickel acetate; The soluble cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate or cobalt acetate; The soluble magnesium salt is one or more of magnesium nitrate, magnesium chloride, magnesium sulfate or magnesium acetate; The soluble copper salt is one or more of copper nitrate, copper chloride, copper sulfate or copper acetate; The soluble aluminum salt is one or more of aluminum nitrate, aluminum chloride or aluminum sulfate.
4. The preparation method according to claim 2, characterized in that: The precipitant is selected from one or a mixture of NaOH, Na2CO3, KOH, K2CO3, and the mass concentration of the precipitant is 2-30%, preferably 5-25%, and more preferably 8-20%; The drying and calcining process described in step (1) is as follows: drying at 100-120°C for 8-14h, and calcining in a muffle furnace at 600-1000°C, preferably 700-900°C, more preferably 750-850°C, for 4-10h, preferably 5-9h, more preferably 6-8h.
5. The preparation method according to claim 2, characterized in that: The soluble phosphate salt is one or more of diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium hypophosphite, potassium hypophosphite or ammonium hypophosphite; the mass concentration of the phosphate salt in water is 0.5-30%, preferably 1-20%, more preferably 2-15%.
6. The preparation method according to claim 1 or 2, characterized in that: The catalyst precursor drying, calcining and reducing process described in step (2) is as follows: drying at 60-80°C for 12h; calcining at 50-500°C, preferably 100-400°C, more preferably 200-300°C under nitrogen for 1-10h; then reducing at 100-800°C, preferably 200-700°C, more preferably 400-600°C under hydrogen for 1-10h; cooling to room temperature; and passivating under nitrogen for 1-10h to obtain the spinel-supported Ni2P catalyst.
7. A bio-oil hydrodeoxygenation catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the hydrodeoxygenation catalyst according to claim 7 in a process of catalyzing the hydrodeoxygenation of bio-oil.
9. The use according to claims 7 to 8, characterized in that: The catalyst is in a high-pressure trickle bed reactor at a reaction temperature of 250-400°C, a reaction pressure of 1-10 MPa, a hydrogen-to-oil ratio of 200-2000, and a liquid hourly space velocity of 0.2-5 h -1 Under certain conditions, oxygen-rich bio-oil can be converted into normal alkanes.
10. The use according to claim 8 or 9, characterized in that: The biological oil is one or more of soybean oil, palm oil, olive oil, peanut oil, jatropha oil, rapeseed oil, cottonseed oil, castor oil and tung oil.
Citation Information
Patent Citations
Hydrogenation deoxidation catalyst for producing biological diesel oil
CN101270300A
Method for preparing diesel components by catalytic hydrodeoxygenation of vegetable oil
CN101709225A
Catalyst for preparing biodiesel through hydrogenation of castor oil and preparation method of catalyst
CN103721741A
Cited By
A bifunctional catalyst for hydrofining of waste plastic cracking oil, a preparation method and application thereof
CN122722280A
